2018
DOI: 10.1111/jdv.15071
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and comorbidities associated with hidradenitis suppurativa in Korea: a nationwide population‐based study

Abstract: The overall prevalence of HS in Korea was lower than that in Western populations, and male patients predominated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
173
4
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(203 citation statements)
references
References 46 publications
(105 reference statements)
16
173
4
3
Order By: Relevance
“…Additional references were identified from reference lists. After application of inclusion and exclusion criteria, 12 studies were included in the systematic review and meta‐analysis (Table ), of which 5 studies had adjusted effect sizes available for extraction. The included study characteristics and demographics of these studies are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Additional references were identified from reference lists. After application of inclusion and exclusion criteria, 12 studies were included in the systematic review and meta‐analysis (Table ), of which 5 studies had adjusted effect sizes available for extraction. The included study characteristics and demographics of these studies are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…33 Atypical cases of HS tend to lack the associations that typical HS have with gender, glucose intolerance, obesity, and metabolic syndrome. Atypical cases of HS may be more predominant in the Malaysian 17 and Asian populations, 34 which explains the lack of association between HS and metabolic syndrome in the study by Loo and colleagues. HS also has other underlying genetic predisposing factors.…”
Section: Discussionmentioning
confidence: 96%
“…More recent epidemiological studies have shown that the majority of HS patients are white; however, these findings are dependent on how and where data are collected and may reflect the racial demographics of the areas in which the studies are conducted . Relatively few studies have investigated HS epidemiology in Asian populations . Using the Korean National Health Insurance database, the prevalence of HS in South Korea is estimated to be 0.06% .…”
Section: Discussionmentioning
confidence: 99%
“…The disease usually presents after puberty with painful, deep-seated, inflamed lesions in the apocrine gland-bearing areas of the body, most commonly the axillary, inguinal and anogenital regions (Dessau definition), all of which negatively affect patients' quality of life (QOL). 1,2 Prevalence of HS varies between Eastern and Western countries, [3][4][5][6] and the clinical manifestations of HS are heterogeneous. 7 Clinical studies from Western countries found that HS is 2-5-times more common in women than in men, with skin lesions more commonly occurring in inguinal and axillary folds and anogenital regions.…”
Section: Introductionmentioning
confidence: 99%